Adverse effects of COVID-19-related lockdown on pain, physical activity and psychological well-being in people with chronic pain. Issue 3 (August 2021) - Fallon, Nicholas; Brown, Christopher; Twiddy, Hannah; Brian, Eleanor; Frank, Bernhard; Nurmikko, Turo; Stancak, Andrej
Countries across the world imposed lockdown restrictions during the COVID-19 pandemic. It has been proposed that lockdown conditions, including social and physical distancing measures, may disproportionately impact those living with chronic pain and require rapid adaptation to treatment and care strategies. Using an online methodology, we investigated how lockdown restrictions in the United Kingdom impacted individuals with chronic pain (N = 431) relative to a healthy control group (N = 88). Data were collected during the most stringent period of lockdown in the United Kingdom (mid-April to early-May 2020). In accordance with the fear-avoidance model, we hypothesised lockdown-related increases in pain and psychological distress, which would be mediated by levels of pain catastrophising. Responses indicated that people with chronic pain perceived increased pain severity, compared to their estimation of typical pain levels prior to lockdown (p < .001). They were also more adversely affected by lockdown conditions compared to pain-free individuals, demonstrating greater self-perceived increases in anxiety and depressed mood, increased loneliness and reduced levels of physical exercise (p ⩽ .001). Hierarchical regression analysis revealed that pain catastrophising was an important factor relating to the extent of self-perceived increases in pain severity during lockdown (β = .27, p < .001) and also mediated the relationship between decreased mood and pain. Perceived decreases in levels of physical exercise also related to perceptions of increased pain (β = .15, p < .001). Interestingly, levels of pain intensity (measured at two time points at pre and during lockdown) in a subgroup (N = 85) did not demonstrate a significant change. However, individuals in this subgroup still reported self-perceived pain increases during lockdown, which were also predicted by baseline levels of pain catastrophising. Overall, the findings indicate that people with chronic pain suffer adverse effects of lockdown including self-perceived increases in their pain. Remote pain management provision to target reduction of pain catastrophising and increase health behaviours including physical activity could be beneficial for this vulnerable population.